a + b = c
There is no definitive answer to this question since it depends on the context in which it is asked. However, one possible interpretation is that it represents the mathematical equation for combining two values (a and b) to equal a third value (c). In other words, if you have two values and you want to calculate a third value that is the equivalent of those two values combined, you would use this equation. So, for example, if you wanted to know what two numbers added together would equal 10, you could use this equation to figure it out: 10 = a + b. In this case, a and b can be any numbers as long as their sum equals 10.
a = b = c
There is no definitive answer to this question since it depends on the values of a, b, and c. However, one possible solution is as follows:
a + b = c
c – b = a
a + c – b = 2a – b (since a + c – b = a + (c – b))
2a – b = a + a -b
2(a-b) = a+a-(2b)
There is no definitive answer to this question as it depends on the specific values of a, b and c. However, one potential interpretation is that a + b = c means that the sum of a and b equals c. In other words, if we have two numbers, a and b, and we add them together to get c, then a + b = c.